Changing Settlement Patterns Sungai Kunyit Laut Village After Development Of International Port In Mempawah District - mukhlis (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2022)
This study aims to describe changes in the settlement pattern of Sungai Kunyit Laut village after the construction of an international port and the impact of changes in community settlement patterns on socio-economic life. This research is a qualitative analysis research using descriptive method. The results of this study indicate a change in the settlement pattern of Sungai Kunyit Laut village after the construction of an international port in Mempawah Regency. From a physical point of view, the settlement pattern has changed from an elongated pattern along the coastline and roadside to a settlement pattern that spreads and clusters and is far from the coast. The resulting impact is a negative impact, namely the narrowness of the fisherman's space so that the level of income decreases and the occurrence of conflicts between the implementing parties and the community who are not satisfied with the results of compensation for land acquisition for buildings and gardens. While the positive impact is that international ports will be integrated with Special Economic Zones (SEZs) to encourage and accelerate West Kalimantan's economic growth by utilizing existing potential.